‘Complex teaching realities’ and ‘deep rooted cultural traditions’: Barriers to the implementation and internalisation of formative assessment in China - Poole, Adam (Cogent OA, 2016)
This article forms the first part of an Action Research project designed to incorporate formative assessment into the culture of learning of a bilingual school in Shanghai, China. It synthesises the empirical literature on formative assessment in China to establish some of the di culties that teachers have faced in trying to incorporate this approach into their teaching. Some of the barriers include student and teacher resistance and notions of face (mianzi) which are also related to deeply held cultural scripts for teaching and learning that emphasise knowledge transmission and respect for the teacher. The article then explores some of the bottom-up solutions that have been suggested by researchers, such as collaborative dialogue, professional development and international perspectives. These suggestions pro- vide a jumping-o point for o ering intercultural communicative competence as a concept and a method that could be e ective in ameliorating cultural discontinuities. Throughout, I show how the difficulties and solutions highlighted by empirical research relate to my own teaching context. Although intercultural communicative competence is not new to China, its application to the internalisation of borrowed policies that include formative assessment has yet to be explored.